Validation and reliability of the Turkish version of Contact Lens Dry Eye Questionnaire-8 (CLDEQ-8). Issue 5 (October 2020) - Dogan, Aysun Sanal; Karabulut, Erdem; Gurdal, Canan
Abstract: Purpose: Contact lens dry eye questionnaire-8 (CLDEQ-8) quantifies the disturbing symptoms with the aim of assessing the satisfaction and overall opinion of contact lens wearers. The aim of this study was to develop Turkish version and to evaluate the validity and reliability of the questionnaire. Methods: CLDEQ-8 was translated into Turkish language, using the back translation methods. In a sample of 10 individuals, validation of translation was checked as pre-test evaluation. Turkish version of CLDEQ-8 questionnaire was conducted in 100 soft contact lens wearers. Validity was investigated using Rasch analysis and reliability by Cronbach's alpha (α) and person separation index (PSI). Results: The participants were healthy other than refractive errors. Their mean age was 25.19 ± 7.03 years and male to female ratio was 14/86. All of them were silicone-hydrogel soft contact lens wearers. Their contact lens history was 3.13 ± 3.77 years and mean refraction error was -2.69 ± 1.64 diopters. The whole 8 items were consistent with the Rasch model (p > 0.05) and unidimensional (paired t test, p = 0.1). Both Cronbach's alpha and PSI values were higher than 0.7 (α = 0.873, PSI = 0.867). There were not functional differences in questionnaire items regarding overall age groups (Andersen LR test, p = 0.518). Conclusion: Turkish version of the CLDEQ-8 conforms to the Rasch model and provides the one dimensional assumption. The questionnaire has internal consistency, is valid and reliable in Turkish contact lens wearers.